Microsurgical vasovasostomy for the treatment ol ntractable chronic scrotal pain after vasectomy - Xiang-An Tu Liang Zhao Liang-Yun Zhao Cai-Mei Zhou Jin-Tao Zhuang Ji-Quan Zhao Kun-Long Lv Xiang-Zhou Sun Shao-Peng Qiu Chun-Hua Deng (亚洲男性学杂志：英文版, 2013)
Dear Editor, We present herein two rare cases of intractable chronic scrotal pain after vasectomy. The patients were effectively treated with microsur-gical vasovasostomy （MVV）. We also discuss the possible aetiologies of the pain and other surgical options.